Case Report: PRES-Like Syndrome With Reversible Cortical Blindness Associated With Essential Thrombocythemia - Li, Ying; Miao, Yuanfeng; Yu, Meng; Zhu, Ying; Liang, Zeyin; Wang, Zhaoxia; Peng, Qing (Frontiers in Neurology, 2021)
Background: There are few reported cases of posterior reversible encephalopathy syndrome (PRES) combined with essential thrombocythemia (ET). We report a case of PRES-like syndrome in ET. Case Report: A 60-year-old man with the history of hypertension and thrombocythemia presented with progressive visual loss after waking up and neurological examination showed pupils were 3mm and equally reactive to light which suggested cortical blindness. Brain magnetic resonance imaging(MRI) revealed restricted diffusion of diffusion weighted imaging（DWI）in bilateral parietal and occipital lobes. Routine blood tests revealed a platelet count of 1044 × 10^9/L. ET was diagnosed after exclusion of other causes. Electroencephalography (EEG) showed periodic triphasic waves in occipital region. The lesions of parietal and occipital lobes on MRI and periodic triphasic waves of EEG disappeared quickly and patient’s vision returned to normal after the treatment with hydroxyurea and sodium bicarbonate. The patient experienced hallucinatory palinopsia during the recovery of vision. Conclusion: ET may be a risk factor for PRES.